C−Boron Enolates Enable Palladium Catalyzed Carboboration of Internal 1, 3‐Enynes. (31st August 2021) - Wang, Ziyong; Wu, Jason; Lamine, Walid; Li, Bo; Sotiropoulos, Jean‐Marc; Chrostowska, Anna; Miqueu, Karinne; Liu, Shih‐Yuan
Abstract: A new family of carbon‐bound boron enolates, generated by a kinetically controlled halogen exchange between chlorocatecholborane and silylketene acetals, is described. These C−boron enolates are demonstrated to activate 1, 3‐enyne substrates in the presence of a Pd 0 /Senphos ligand complex, resulting in the first examples of a carboboration reaction of an alkyne with enolate‐equivalent nucleophiles. Highly substituted dienyl boron building blocks are produced in excellent site‐, regio‐, and diastereoselectivity by the described catalytic cis ‐carboboration reaction. Abstract : A new family of carbon‐bound boron enolates, in cooperation with a Pd complex supported by an 1, 4‐azaborine‐derived phosphine ligand, transforms enynes into highly substituted dienyl boronates in exquisite site‐, regio‐, and cis ‐diastereoselectivity.